2017
DOI: 10.1016/j.neuroscience.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Xanthurenic Acid Formation from 3-Hydroxykynurenine in the Mammalian Brain: Neurochemical Characterization and Physiological Effects

Abstract: Xanthurenic acid (XA), formed from 3-hydroxykynurenine (3-HK) in the kynurenine pathway of tryptophan degradation, may modulate glutamatergic neurotransmission by inhibiting the vesicular glutamate transporter and/or activating Group II metabotropic glutamate receptors. Here we examined the molecular and cellular mechanisms by which 3-HK controls the neosynthesis of XA in rat, mouse and human brain, and compared the physiological actions of 3-HK and XA in the rat brain. In tissue homogenates, XA formation from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 71 publications
(99 reference statements)
1
38
0
Order By: Relevance
“…However, on the other hand, there is recent preclinical evidence that has shown that 3HK also have the ability to decrease the excitatory postsynaptic potentials at hippocampus, so perhaps through these mechanisms 3HK can also have a negative effect on the learning and memory processes in patients with PSD. 46,47 Interestingly, when dividing patients with poor or good sleep quality in our study, we also found a significant increase in serum levels of 3HK in patients with poor sleep quality, which may be in accordance with previous experimental studies in where increase of Kyns brain levels in rats produces a reduction in the duration of REM (rapid eye movement) sleep, alterations in sleep architecture, and cognitive deficits. 48 However, the role of Kyns in the physiology of sleep and its disorders has not yet been adequately studied.…”
Section: Discussionsupporting
confidence: 92%
“…However, on the other hand, there is recent preclinical evidence that has shown that 3HK also have the ability to decrease the excitatory postsynaptic potentials at hippocampus, so perhaps through these mechanisms 3HK can also have a negative effect on the learning and memory processes in patients with PSD. 46,47 Interestingly, when dividing patients with poor or good sleep quality in our study, we also found a significant increase in serum levels of 3HK in patients with poor sleep quality, which may be in accordance with previous experimental studies in where increase of Kyns brain levels in rats produces a reduction in the duration of REM (rapid eye movement) sleep, alterations in sleep architecture, and cognitive deficits. 48 However, the role of Kyns in the physiology of sleep and its disorders has not yet been adequately studied.…”
Section: Discussionsupporting
confidence: 92%
“…S11). The constancy of the 3-HK level, along with the accumulation of its product, XA, under extremely harsh conditions such as occur during anhydrobiosis suggests that kynurenine aminotransferase (KAT), which catalyzes the processing of KYN to KA and 3-HK to XA in mammals (44,45), remains highly effective during drought, which may be important for survival. In insects there is insufficient information about the enzymes involved in the transamination reaction of KYN and 3-HK, but it is usually assumed that a similar form of KAT is present (41).…”
Section: Dynamics Of Adenylates: Optimal Energy Storage For Rapidmentioning
confidence: 99%
“…Moreover, XA produced by Anopheles gambiae 3-hydroxykynurenine transaminase (Rossi et al, 2005, 2006) is a trigger for Plasmodium male gametogenesis, which takes place in the mosquito upon a parasite-infected blood meal (Billker et al, 1998). XA also exerts multiple actions in the mammalian brain (Sathyasaikumar et al, 2017; Schwarcz and Stone, 2017). Of particular significance is the observation that levels of XA are reduced in the brain and serum of schizophrenic patients, which is opposite to what has been reported for KYNA (Fazio et al, 2015).…”
Section: Future Directions For Kat Structural Investigationsmentioning
confidence: 99%
“…Of particular significance is the observation that levels of XA are reduced in the brain and serum of schizophrenic patients, which is opposite to what has been reported for KYNA (Fazio et al, 2015). By using different approaches, including in vivo analyses, it has been proposed that KAT II could be the main determinant of XA synthesis in the CNS (Sathyasaikumar et al, 2017). Although XA and KYNA production appears to be sustained by distinct brain cell populations (Roussel et al, 2016), these studies highlight the need to analyse the whole complement of KAT isozymes for their role in XA synthesis and to re-evaluate the impact of specific KAT inhibitors on the local balance of these two fundamental products of the KP.…”
Section: Future Directions For Kat Structural Investigationsmentioning
confidence: 99%